Combating banana bunchy top disease: an interview with the Kasese district agricultural officer - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
From 3rd to 4th October 2024, 71 stakeholders, including 41 smallholder farmers from the districts of Bushenyi, Rubirizi, Bunyangabu and Kasese districts, staff from IITA, ASARECA, Plant Health Initiative, MAAIF, NARO, Extension Agents, and local policy makers gathered in Kasese district for a comprehensive 2-day learning experience about the emerging BBTD caused by the invasive Banana Bunchy Top Virus (BBTV).